ECF chemotherapy for liver metastases due to castration-resistant prostate cancer - Gupta, Shruti; Potvin, Kylea; Ernst, D. Scott; Whiston, Frances; Winquist, Eric (Canadian Urological Association Journal, 2014)
Introduction: Most men with metastatic castration-resistant prostate cancer (CRPC) have biochemical response to docetaxel, but the objective response rate is low. Liver metastases are uncommon with CRPC and associated with shorter survival. More active treatment might benefit these patients. Epirubicin, cisplatin and flurouracil (ECF) is a standard regimen for gastric cancer and response in CRPC liver metastases has been reported. We reviewed our experience with ECF in CRPC with the primary objective of determining its anti-tumour activity in patients with liver metastatic CRPC. Methods: Men with CRPC treated with ECF were identified from electronic databases and data were extracted from medical records. Men with tumours showing neuroendocrine features were excluded. Results: In total, we identified 14 CRPC patients treated with ECF, of which 8 had liver metastases. The median age was 56 (range: 42-76) and all had multiple poor prognostic features. A median of 6 cycles of ECF were administered (range: 1-10) and toxicities were similar to previous reports. Of the 8 patients with liver metastases, 5 had partial remission. Conclusions: ECF was highly active in this small selected group of younger men with liver metastases from CRPC and multiple poor prognostic features. Despite important limitations, this is the third report of high objective response rates with ECF in CRPC. Objective response rates are low with current monotherapies. A higher probability of ORR is preferred for critical organ disease, therefore the anti-tumour activity should encourage testing of ECF in comparison to the most active current therapies.